Regional patterns of transport CO₂ and total CO₂ emissions in the EU15 countries - Petri Tapio; Jyrki Luukkanen (European Regional Science Association (ERSA), 2003)
The decarbonisation of the economy is a well-established international trend in environmental research. Decarbonisation is normally defined as a decreasing carbon intensity of the economy, measured by dividing the carbon dioxide (CO2) emissions with the gross domestic product (GDP). The paper compares two aspects of the carbon intensity of the economy: (1) The total CO2 emission intensity of the economy and (2) the transport CO2 emission intensity of the economy. Data is gathered from the current fifteen European Union (EU15) countries from 1960 to 1999. The countries are grouped by cluster analysis and regional patterns of the groupings are analysed. It can be concluded that while the total CO2 intensity of the economy has decreased, the transport CO2 intensity has in fact increased in the EU15 countries. Regarding the whole period, only Ireland and Austria showed decreasing transport CO2 intensity. It seems, that in the 1990's a change in the trend was achieved also in Denmark, Finland, Sweden and United Kingdom. In the United States, transport CO2 intensity began to decrease already in the mid 1970's, but still in 1999 the figures were approximately two times greater than that of the EU15. Key words: carbon dioxide emissions, transport, carbon intensity, european union
Keywords: 330